ANESTESI PADA GASTROSCHISIS - ANDRI YUNAFRI (LP2MTBM MAKARIOZ, 2019)
Gastroschisis is a defect in the anterior abdominal wall usually on the right side, caused by a herniation of the abdominal contents without being protected by a pouch, repairing the operation is an action that must be done immediately. Gastroschisis is different from omfalocele, where gastroschisis has other abnormalities that are fewer and are not associated with chromosomal abnormalities. The incidence of this defect is 1 in 10,000 births. Perioperatively monitors loss of fluid and body heat with general anesthesia techniques.